Anxiety-related behaviors without observation of generalized pain in a mouse model of endometriosis - Nunez-Badinez, Paulina; Laux-Biehlmann, Alexis; Hayward, Michael D.; Buiakova, Olesia; Zollner, Thomas M.; Nagel, Jens (Frontiers in Behavioral Neuroscience, 2023)
Endometriosis is a chronic, hormone-dependent, inflammatory disease, characterized by the presence and growth of endometrial tissue outside the uterine cavity. It is associated with moderate to severe pelvic and abdominal pain symptoms, subfertility and a marked reduction in health-related quality of life. Furthermore, relevant co-morbidities with affective disorders like depression or anxiety have been described. These conditions have a worsening effect on pain perception in patients and might explain the negative impact on quality of life observed in those suffering from endometriosis-associated pain. Whereas several studies using rodent models of endometriosis focused on biological and histopathological similarities with the human situation, the behavioral characterization of these models was never performed. This study investigated the anxiety-related behaviors in a syngeneic model of endometriosis. Using elevated plus maze and the novel environment induced feeding suppression assays we observed the presence of anxiety-related behaviors in endometriosis-induced mice. In contrast, locomotion or generalized pain did not differ between groups. These results indicate that the presence of endometriosis lesions in the abdominal cavity could, similarly to patients, induce profound psychopathological changes/impairments in mice. These readouts might provide additional tools for preclinical identification of mechanisms relevant for development of endometriosis-related symptoms.